KORELASI KONDISI FISIK RUMAH DAN KARAKTERISTIK BALITA DENGAN KASUS CAMPAK DI KOTA SURABAYA - Birayu Jeny Afdhalash; Retno Adriyani (Universitas Airlangga, 2019)
There were 61 confirmed cases of measles in Surabaya in 2016, whereas in January-May 2017 there were 52 confirmed cases of measles. Many factors that could affect the incidence of measles include physical conditions of the house (lighting, occupancy density, and ventilation area) and toddler characteristics (age, gender, immunization status of measles, exclusive breastfeeding and contact history ). The purpose of this study was to analyze the relationship between physical conditions of the house and toddler characteristics with the incidence of measles in Surabaya. It was an observational study in the form of case study control design. This study used all confirmed measles cases on toddlers during January-May 2017 which had been proven by IgM laboratory examination by Health Office of Surabaya City. The results of this study indicated that there was a significant correlation between lighting (approx.sig=0.025), occupancy density (approx.sig=0.001), immunization status (approx.sig=0.136) and contact history with measles incident on toddlers in Surabaya. The conclusions of this study were the conditions of lighting, density, measles immunization status and contact history were significant risk factors for the incidence of measles. Mothers should maintain the cleanliness of the home environment, and toddler’s bedroom should get enough sunlight and have good air circulation by opening windows to prevent the growth of measles virus.